Eksistensi Perempuan Pemecah Batu Suplit Dalam Meningkatkan Pendapatan Keluarga : (Studi Di Desa Mantobua Kecamatan Lohia Kabupaten Muna) - Farni; Peribadi; Amin Tunda (Jurnal Neo Societal, 2026)
This study aims to determine the role of women stone crushers in improving the family economy in Mantobua Village, Lohia District, Muna Regency, and to determine the impact of working as stone crushers on the health and safety of women in Mantobua Village, Lohia District, Muna Regency. The results indicate that women's involvement in stone crushers is motivated by economic needs, a desire for independence, and an effort to help meet family needs. The income earned is variable but plays a significant role as a supplement to household income. In addition to economic benefits, this work also fosters a sense of responsibility, independence, and self-confidence. However, women face several obstacles, such as physical exhaustion, health risks, simple work tools, and uncertainty about prices and demand. In conclusion, women stone crushers make a significant contribution to improving the family economy, although they still need support in the form of training, more appropriate work tools, and government attention to ensure their welfare and occupational safety.